Experience of Meningovascular Syphilis in Human Immunodeficiency Virus Infected Patient - Lee, Jung-Pyo (The Korean Neurosurgical Society, 2009)
Since the start of the antibiotic era, syphilis has become rare. However, in recent times, it has tended to be prevalent concomitantly with human immunodeficiency virus (HIV) infection and coinfection in North America and Europe. Now, such cases are expected to increase in elsewhere including Korea. A 40-year-old male patient visited hospital complaining of a headache for about one month. Brain computed tomography and magnetic resonance imaging, showed leptomeninged enhancing mass with edema an right porisylvian region, which was suspected to be glioma. Patient underwent a blood test and was diagnosed with syphilis and acquired immune deficiency syndrome. Partial cortical and subcortical resection were performed after small craniotomy. The dura was thick, adhered to the brain cortex, and was accompanied by hyperemic change of the cortex. The pathologic diagnosis was meningovascular syphilis (MS) in HIV infection. After the operation, the patient was treated with aqueous penicillin G. Thereafter, he had no neurological deficit except intermittent headache. At first, this case was suspected to be glioma, but it was eventually diagnosed as MS in HIV coinfection. At this point the case was judged to be worth reporting.